KOORDINASI HORMON TUMBUHAN DALAM MENGHADAPI STRES KEKERINGAN - Meilani Wulandari; Wan Syafi'i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Drought stress triggers complex physiological and molecular responses coordinated by plant hormones. This article aims to describe the hormonal interactions that regulate growth, water balance, and cellular protection during drought conditions. The study uses a literature review approach based on recent primary sources published in the last ten years. Findings indicate that abscisic acid (ABA) acts as the central regulator by inducing stomatal closure, modulating stress-responsive genes, and interacting with other hormones including auxin, cytokinin, ethylene, salicylic acid, and jasmonic acid. Auxin and cytokinin generally suppress drought tolerance by promoting growth processes; meanwhile, plants reduce the levels of both hormones during dehydration. Ethylene and jasmonic acid contribute to root architecture modification and stress signaling. The synergy among these hormones forms an adaptive network enabling plants to optimize water uptake, maintain cellular integrity, and adjust metabolism. The conclusion emphasizes that drought resilience is not controlled by a single hormone, but through dynamic, interconnected hormonal crosstalk that reprograms plant physiology under limited water availability.